Covid-19 pandemic and global tourism - Luković, Stevan; Stojković, Dragan (Hotel and Tourism Management, 2020)
The tourism industry represents a significant part of the global economy. However, tourism demand is very sensitive to crisis events, such as economic crises, epidemics, pandemics, natural disasters and terrorist attacks. Regarding this, the primary research goal of the paper is to analyze the impact of the Covid-19 disease on global tourism. During 2020, in order to prevent further spread of this contagious disease, almost all countries in the world have introduced a ban on movement, closing of borders and other important health measures. The review of the relevant literature provided in the paper shows that the introduced measures have a negative impact on the global hospitality, travelling and tourism industry.